Traditional Ucing-ucing Game in an Effort to Strengthen Children's Character as an Implementation of AUD Play and Games Courses - Royani, Ida; Katoningsih, Sri; Suriyani, S (Early Childhood Research Journal (ECRJ), 2023)
Children are the foundational generation for the development of a country, so character formation must be done from an early age. Nowadays children are less interested in traditional games and prefer games on gadgets. Teachers have a role in strengthening character. The purpose of this study is to apply the traditional game of ucing-ucing in play and games courses to strengthen the character of early childhood. It is hoped that the results of this research can be useful for prospective PGPAUD teachers so that they are motivated and be creative in the learning process. This research employs the Classroom Action Research (CAR). Data collection techniques use observation, interview, and test techniques (cycle 1 and cycle 2). The results show that there is an increase in quite a variety of traditional games that need to be explored and developed, one of which is the ucing-ucing game because it contains values such as honesty, responsibility, and cooperation. By using the traditional games, children can maintain concentration, knowledge, attitudes, skills and agility, which are purely carried out by the human brain and body. The results of observations in cycles 1 and 2 experienced an increase from 65% to 85%.